Assessment of uncertainties associated with the use of alternative satellite-based rainfall estimates in Pitman modelling - Kibii, Joshua Kiprotich (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2024.